Analisis Metode Hermeneutika dalam Al-Qur’an atas Pemikiran Nasr Hamid Abu Zaid - Hafid Nur Muhammad; Tedi Turmudzi, dkk. (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2022)
By examining the thoughts of Nasr Hamid Abu Zaid in interpreting the Qur'an through the Hermeneutic method, this paper tries to analyze the theories and methods of interpretation. In addition to criticizing his thinking in hermeneutics, and the modern approach to the Qur'an, Abu Zaid views, there are 2 goals in his study of the Qur'an. The first is to reconnect the study of the Qur'an with literary theory and criticism. In this case, the Qur'an is a linguistic text and cannot be separated from culture and history. Therefore, cultural and historical texts must be studied using linguistic and literary approaches, including hermeneutics and semiotics. The second is to define an